The Philosophy of Atadiken in the Lamaholot Tribe of East Nusa Tenggara: A Proposition for an Epistemological Foundation of Religious Moderation in Indonesia - Dore Woho Atasoge, Anselmus; Yulita C.Age, Maria; Sabu Kopong, Primiaty; Adrianus Sihombing, Adison (Center for Research and Development of Religious Literature and Heritage, 2024)
This study aims to explore the Atadiken philosophy in the Lamaholot community, especially on their perspectives and practices on humanity. A qualitative research was conducted, employing field observations and structured interviews with 45 informants from three islands in East Flores Regency: East Flores mainland, Adonara, and Solor. Research participants include traditional leaders, religious figures, educators, and youth from the two main religions in East Flores. The study finds that the Lamaholot Atadiken philosophy can serve as an epistemological foundation to support and develop religious moderation in Indonesia. Atadiken’s philosophy views humanity as kin, recognizing, valuing, respecting, and protecting individuals as dignified beings. This reinforces key terms in religious moderation, such as humanity, collective welfare, justice, tolerance, commitment to shared agreements, non-violence, and love for the nation and tradition. With its core emphasis on humanity, Atadiken’s philosophy promotes religious moderation and social harmony, aligning with both local and global religious ideals.